Thyroid Hormone Induces PGC-1α during Dendritic Outgrowth in Mouse Cerebellar Purkinje Cells - Hatsukano, Tetsu; Kurisu, Junko; Fukumitsu, Kansai; Fujishima, Kazuto; Kengaku, Mineko (Frontiers in Cellular Neuroscience, 2017)
Thyroid hormone 3,3’,5-Triiodo-L-thyronine (T3) is essential for proper brain development. Perinatal loss of T3 causes severe growth defects in neurons and glia, including strong inhibition of dendrite formation in Purkinje cells in the cerebellar cortex. Here we show that T3 promotes dendritic outgrowth of Purkinje cells through induction of peroxisome proliferator-activated receptor gamma co-activator 1α (PGC-1α), a master regulator of mitochondrial biogenesis. PGC-1α expression in Purkinje cells is upregulated during dendritic outgrowth in normal mice, while it is significantly retarded in hypothyroid mice or in cultures depleted of T3. In cultured Purkinje cells, PGC-1α knockdown or molecular perturbation of PGC-1α signaling inhibits enhanced dendritic outgrowth and mitochondrial generation and activation caused by T3 treatment. In contrast, PGC-1α overexpression promotes dendrite extension even in the absence of T3. PGC-1α knockdown also downregulates dendrite formation in Purkinje cells in vivo. Our findings suggest that the growth-promoting activity of T3 is partly mediated by PGC-1α signaling in developing Purkinje cells.